New species of and keys to South American Gripopterygidae (Plecoptera) - McLellan, Ian D. (Illiesia, 2007)
Uncicauda pirata new genus and species and Alfonsoperla flinti new genus and species are described. The larvae of the following named species are either described for the first time (1st) or corrected (cd) descriptions given: Antarctoperla altera (1st), Aubertoperla illiesi (cd), Aubertoperla kuscheli (cd), Claudioperla tigrina (cd), Limnoperla jaffueli (cd), Rhithroperla rossi (cd), Teutoperla spp. (1st). We also describe larvae of four Antarctoperlinae species that cannot be associated with adults; these new larvae are therefore not named. The larvae of the South American Gripopterygidae are keyed to genus, and some to species.
Keywords: insekti; Plecoptera; vrbnice; Južna Amerika